Selection Model for Optimization of the Gene Bank of Cherry (Prunus cerasus L.) and plum (Prunus domestica L.) in the Low Volga Region - Solonkin, Andrey; Nikolskaya, Olga; Kikteva, Yelena (KnE Life Sciences, 2019)
The researchers of the Scientific Research Institute of Agriculture of the Low Volga region – the branch of FSC of agroecology of RAS – have developed the regulations for the selection model of optimization of genetic pool and created a number of varieties of cherry and plum by hybridization of local and southern varieties and by use of hybrids of free pollination. The optimization of gene bank of cherry and plum on the basis of the study of genetic biodiversity and regulations for the selection model and programs provides the adaptation of the newly developed varieties for the creation of industrial crops in agrosystems of the Low Volga and other regions of Russia. The catalog of assortment has been developed and the six varieties of garden plum (Prunus domestica L.) regionalized, including Volgogradskaya, Bogatyrskaya, and Vengerka korneyevskaya varieties, as well as a number of other ones that have been created during hybridization of the local varieties of the Volga region, such as, Volzhskaya sinyaya, Ternosliv letniy, Ternosliv osenniy with the most adaptive introduced varieties. The new varieties and elites (best specimens) of sour cherry (Prunu scerasus L.): Loznovskaya, Dubovskaya krupnoplodnaya, Melodiya, Lyubimitsa, Peskovatskaya, Dubovochka, Temnookrashennaya, Sharada, Pamyat‘ Zhukovoy – have been selected by intervarietal hybridization and by sowing of seeds collected during free pollination of the following varieties: Zhukovskaya, Lyubskaya, Krasa Severa, Shirpotreb chernaya, Ujfeherto furtos. The above-mentioned forms contributed to a richer assortment of garden plum and sour cherry in the Low Volga region, meaning adaptive, high-yielding, high-quality varieties of universal use. There is a good reason to use the above-mentioned assortment as the integrated donors during the development of selection programs aimed at continued improvement of varieties of stone fruit crops.